Enhancement of the antioxidant defense system of post-harvested 'Daw' longan fruit by chlorine dioxide fumigation - Chomkitichai,W. (Elsevier, 2015)
© 2014 Elsevier B.V. The response of the antioxidant defense system to chlorine dioxide (ClO2) of post-harvested 'Daw' longan fruit was determined. Fresh fruit was fumigated with 10mg/L ClO2 for 10min and then packed into cardboard boxes and stored at 25±1°C with 82±5% RH for 7 days. Changes in free radicals elimination systems were examined every day. The activities of enzymatic antioxidants including superoxide dismutase, catalase and ascorbate peroxidase in non-fumigated fruit (control) increased and reached the peak on day 2 and decreased thereafter. The contents of non-enzymatic antioxidant such as total phenolic compounds, ascorbic acid (ASA), total glutathione, α-tocopherol and total antioxidant capacities (TAC) decreased continuously throughout storage time. These decreases coincided with the onset of pericarp browning. ClO2 fumigation enhanced the antioxidant defense system of longan fruit during storage which was associated with less pericarp browning. The enzymatic antioxidant activities, non-enzymatic antioxidant contents and TAC showed significantly higher levels in the ClO2 treated fruit than those in the control throughout the storage period. It was concluded that enhanced antioxidant defense system by ClO2 alleviates browning in 'Daw' longan during storage.